Meat characteristics from four different cutting parts of Cherry Valley duck - Chanporn Chaosap; Panneepa Sivapirunthep (My University, 2018)
The objective of this study was to investigate the duck meat characteristics in 4 main parts : breast, fillet, leg, and thigh. A total of 30 Cherry Valley ducks were used in this study. They were slaughtered at the age of 42 days. Carcasses were cut and collected the boneless and skinless of breast, fillet, leg, and thigh for measuring meat characteristics. The results showed that fillet and leg had the longest sarcomere length at 6, 12, and 24 hour post mortem (P<0.05). The highest pH was from leg and the lowest pH was from breast and fillet (P<0.01). The cooking loss percentage of breast was the highest while the lowest was from leg (P<0.01). Thigh and leg were tougher than breast and fillet. Shear force value negatively correlated with sarcomere length at 24 hour post mortem and with pH but positively correlated with L* value.
Keywords: Fillet (mechanics); Chicken breast; Animal Nutrition and Physiology